A critical barrier analysis framework to the development of rural distributed PV in China. (15th April 2022) - Wu, Yunna; Xu, Minjia; Tao, Yao; He, Jiaming; Liao, Yijia; Wu, Man
Abstract: Rural distributed photovoltaic (PV) is conducive to low-carbon development of China. Nevertheless, the development is hampered by multiple barriers and therefore lags behind expectations. Some studies have been devoted to this, but there are still problems including incomplete identification of obstacles and non-objective analysis methods. Thus, this paper is dedicated to establishing a complete and objective research framework to effectively identify obstacles and promote high level development of rural distributed PV. Firstly, a two-stage process is adopted to extract obstacles from the entire life cycle of rural distributed PV, and 10 obstacles are identified. Then the K-means clustering algorithm are introduced to improve the DEMATEL-ISM method for threshold determination and barrier analysis. Interactions between obstacles are divided into three levels and a network hierarchy that reflects these interactions is created. The results show that imperfect policies and regulations, diminished subsidy, high initial investment and aging equipment and poor quality are critical barriers, and corresponding suggestions on the collaboration between enterprises and the government are put forward. This paper comprehensively studies the obstacles to the development of rural distributed PV by objective methods and proposes suggestions for improvement, which is beneficial to the development of rural distributed PV in China. Highlights: A comprehensive barrier system of rural distributed PV projects is established. K-means clustering algorithm is introduced to improve DEMATEL-ISM method. The mechanism of barriers affecting the rural distributed PV are determined. A series of recommendations for rural distributed PV are proposed.